Illicit drug use among New Zealand gay and bisexual men: Prevalence and association with sexual health behaviours. (25th April 2017) - Saxton, Peter; Newcombe, David; Ahmed, Arslan; Dickson, Nigel; Hughes, Anthony
Abstract: Introduction and Aims: Data are lacking on drug use among gay and bisexual men (GBM) in New Zealand. We establish a baseline estimate of drug use and investigate associations with sexual health and HIV risk. Design and Methods: A cross‐sectional survey of GBM was conducted in gay community settings and online. Participants were asked their frequency of using nine drugs (poppers, cannabis, ecstasy, methamphetamine, amphetamine, cocaine, LSD, gamma hydroxybutyrate and ketamine) in the previous 6 months. We examined associations between selected drugs and number of recent partners, unprotected anal intercourse with a casual partner and sexually transmitted infections using adjusted odds ratios (AOR). Results: Overall, 3211 participants provided information of whom 55.8% reported any drug use, and 37.9% cannabis, 36.7% poppers, 16.5% ecstasy, 10.5% amphetamine, 7.4% methamphetamine, 6.6% LSD, 6.1% cocaine, 5.3% gamma hydroxybutyrate and 4.4% ketamine use. A quarter of all respondents (25.6%) reported using one drug, 22.8% two to four and 7.4% five or more drugs (polydrugs). Methamphetamine and polydrug use was independently predictive of reporting >20 recent partners (AOR 1.6 and 7.0, respectively), unprotected anal intercourse with a casual partner (AOR 1.8 and 3.2, respectively) and a sexually transmitted infection (AOR 1.6 and 4.3, respectively). Discussion and Conclusions: Drug use was common in this sample of GBM. Polydrug and methamphetamine users had especially high sexual health needs, but risks remained elevated among GBM consuming other drugs. Drug harm reduction programs and HIV prevention should target GBM with problematic drug use. Limitations include an inability to attribute causation. [Saxton P, Newcombe D, Ahmed A, Dickson N, Hughes A. Illicit drug use among New Zealand gay and bisexual men: Prevalence and association with sexual health behaviours. Drug Alcohol Rev 2017;00:000‐000]